Supporting Strategic Success through Enterprise-Wide Reputation Risk Management - Gatzert, Nadine; Schmit, Joan (The Journal of Risk Finance, 2015)
Purpose – The purpose of this paper is to present a coherent and effective enterprise risk management (ERM) framework that includes necessary steps and processes for integrating reputation risk management into an organization’s overall ERM approach which is intended to support corporate strategic success. In particular, reputation creation, enhancement, and protection are critical to an organization’s success, yet highly challenging given the wide ranging and somewhat opaque nature of the concept. These qualities call for a strong ERM approach to reputation that is holistic and integrative, yet existing knowledge of how to do so is limited. Design/methodology/approach – The paper evaluates and synthesizes existing reputation literature in developing an enterprise-wide reputation risk management framework incorporating necessary steps, processes, and considerations. We address risk strategy, risk assessment, risk governance, and risk culture as key elements of ERM and conclude with suggestions for future research. Findings – The results suggest several important ideas which are of great relevance when integrating reputation risk management into an ERM framework. Among these are the importance of: identifying and understanding the purpose of key stakeholders, appreciating the multidimensional and layered effect of events on organizational reputation and monitoring the influence of technological advances. Originality/value – The authors contribute to the literature by developing a framework for enterprise-wide reputation risk management that applies across industries. In contrast to previous work, the authors offer a broader perspective on the underlying causes and consequences of reputation damage based on empirical evidence and insight from the academic literature and provide additional detail in identification of reputation determinants, antecedents, and drivers. While much of this information exists in various places in the literature, it has not been organized into a cohesive framework nor used in developing an ERM strateg
Keywords: Corporate reputation; Reputation risk; Reputation risk management; Reputation risk response